Penerapan Algoritma Brute Force dalam Pencarian Kamera pada Aplikasi Penyewaan Kamera - Farrel Zacky As Syahid Ramadhani; Aqief Idlan Hakimi; M. Dzaka Al Fikri; Rafif Ghani Widiandhi; Cherin Adelia Syakil; Tedy Setiadi (Computer Science and Information Technology, 2024)
The demand for high-quality cameras in various activities is increasing, driving the development of the camera rental industry. The implementation of efficient search algorithms in camera rental systems has become very important to improve user experience. Brute Force Algorithm, although simple, offers an effective solution for data search. This study aims to explore the application of the Brute Force Algorithm in camera search in camera rental applications and identify potential improvements to enhance the efficiency of the algorithm. The results show that the Brute Force Algorithm is reliable in scenarios where ease of implementation and flexibility are top priorities. The implementation of this algorithm results in an effective and user-friendly camera rental application, allowing users to find the desired camera quickly and accurately.